The uncharted danger of living in the tropics: A needlefish impalement of the sigmoid colon - Muhamad, A.; Ali, A.A.; Firdaus Hayati; Zakaria, A.D. (Universiti Putra Malaysia Press, 2020)
Penetrating injury to the abdominal viscera is not uncommon unless when it is caused by marine life. We present a 39-year-old fisherman from a tropical country who had sustained a penetrating injury from a stab wound to the abdomen due to needlefish impalement. He sustained a small perforation of the sigmoid colon during exploratory laparotomy and primary repair was done. Although this incident is rare, there are cases involving seawater activities either for leisure, sport or diving for fishing. We highlight this rare incident and discuss the management plan.